Histological study to the effect of Potassium Dichromate on the reproductive organs in mature rats - Firas Abbas Hussain Al-saadi (Tikrit Journal of Pure Science)
This study was designed to show the effect of potassium dichromate (24 mg/kg orally for 60 day) in mature male and female. The results of experiment in male rats showed decrease in seminiferous epithelia thickness and number of stage VII cells (spermatogonium, spermatocytes, spermatids) at the same time the experiment of immature female rats treated with potassium dichromate showed increase in the diameter of ovarian follicles in the categories (101-200), (201-300) and (<400) .It was concluded that potassium dichromate has detrimental effects on living tissue and in some sexual parts in both sexes (male and female) .